Case Report: A case of sudden death due to occupational nicotine poisoning: clinical presentation and MRI findings - Jianjian Liu; Zhaozhao Shan; Zhaozhao Shan; Xiangdong Jian; Xiangdong Jian; Baotian Kan (Frontiers in Pharmacology)
BackgroundNicotine is a toxic alkaloid commonly found in tobacco products. This paper presents the clinical case of a patient who was exposed to a nicotine-laden waste liquid.Case presentationA 24-year-old male arrived at a local hospital in a state of coma and cardiac arrest. Following successful cardiopulmonary resuscitation, he was transferred to our facility for further treatment. Magnetic resonance imaging of the patient’s head and neck revealed bilateral ischemic infarctions in the hippocampal region. After 24 days of treatment, the patient was discharged with significant improvement.DiscussionThis case highlights the potential for severe clinical manifestations to arise shortly after a single exposure to a substantial amount of nicotine.ConclusionIn clinical practice, it is crucial to promptly assess the patient’s occupational history to identify the cause of the condition, closely monitor vital signs, and provide active supportive and symptomatic care. Additionally, this case underscores the importance of ensuring production safety and increasing awareness regarding occupational exposure risks.